The effect of Sr modification on thermal diffusivity of Al–8Si alloy. (4th March 2018) - Vijayan, Vijeesh; Prabhu, K. Narayan
Abstract: Newtonian and Fourier analysis techniques were used to calculate the solid fraction and latent heat during the solidification of Al–8Si alloy and the subsequent results were used to study the effect of Sr modification on thermal diffusivity of the solidifying melt. The results indicate that the thermal diffusivity increased significantly with increase in Sr content. The increase in the thermal diffusivity was attributed to the increase in the electronic conduction of the modified alloy due to the decreased activity of the bifilm. The results also indicate that the latent heat evolved during solidification increased with increase in Sr concentration and was associated with the increase in the solidification range that occurred during the modification process.